Pendampingan Manajemen Aset Bagi UMKM Desa Pundenarum, Karangwen Kabupaten Demak - Puspitasari, Ratih Hesty Utami; Ervina I, Rr. Hawik; Indriasari, Ika; Sobaruddin A, Shofif (Fokus ABDIMAS, 2023)
The study aims to analyze the situation of the UMKM industry in the Desa Pundenarum, Kecamatan Karangawen Kabupaten Demak, and its impact on the management of assets. The study focuses on the importance of aset as a crucial component of a company that must be managed effectively and efficiently to achieve the desired results. The study consists of several steps, including determining the status of the aset, inventarisasi kekayaan dan masa pakai aset, menjaga nilai aset tinggi dengan usia panjang, minimisasi biaya, menghasilkan manfaat optimal, and pengamanan aset. By implementing these steps, the company can minimize risks related to the aset's performance, thereby enhancing the performance of the company. The study is conducted on 20 participants from the UMKM industry in the Desa Pundenarum, Kecamatan Karangawen Kabupaten Demak. The agenda includes the study of aset, klasifikasi aset, and manajemen aset yang terdiri dari enam siklus yang terdiri inventarisasi aset, penilaian aset, dan optimalisasi aset. The study also focuses on the importance of the aset's performance in the management of assets in the UMKM industry. By implementing these steps, the company can optimize its assets and achieve the desired results, ultimately contributing to the overall success of the UMKM industry in the Desa Pundenarum, Kecamatan Karangawen Kabupaten Demak.